PENGARUH PEMBERIAN PARE (MOMORDICA CHARANTIA) TERHADAP PERUBAHAN HISTOPATOLOGIS PADA USUS TIKUS YANG TERINFEKSI ESCHERICHIA COLI - Putri, Sabrina Herfika; Tofrizal, Alimuddin; Sy, Elmatris; Asri, Aswiyanti; Rita, Rauza Sukma; Putra, Syandrez Prima (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Bitter melon (Momordica charantia) has been empirically proven for antimicrobial properties that can be used as an alternative medicine, while the changes that occur in Escherichia coli-infected mouse intestine after administering bitter melon have not been widely studied. The aim of this study was to determine the effect of Momordica charantia administration on histopathology of intestine of E. coli infected mice. This research was post-test control randomized group study involving 20 mice’s small intestine paraffin blocks which were divided into 4 groups consisted of control and different dosage of bitter melon juice, observed subsequently under a microscope to measure the of the small intestine lining and assess inflammation using modified Barthel Mandja scoring. This study found significant changes the height of mucosa and villi of mice small intestine after administration of 100 grams of bitter melon juice and the muscle layer and crypts after administration of 200 grams of bitter melon juice. The Barthel Manja score showed decrease of inflammation degree among P2 group, while increased inflammation degree found in P3 group. It can be concluded that administration of bitter melon juice has the potential to improve the intestinal histopathology of mice infected with Escherichia coli.